Keterlibatan ASN dalam Politik Praktis Pemilu dan Implikasinya bagi Demokrasi dalam Tinjauan Hukum Tata Negara - Firdaus, Muhamad Iqbal Ansori; Safitri, Widi; Andriyanthy, Indri Zahra; Maharani, (SIYASI: Jurnal Trias Politica, 2025)
This study examines the involvement of State Civil Apparatus (ASN) in practical electoral politics and its implications for democracy from a constitutional law perspective. ASN, as part of the state bureaucracy, are required to maintain neutrality to ensure honest, fair, and democratic elections. However, the reality on the ground shows that violations of ASN neutrality persist, manifested in support for certain candidates, both directly and through social media. The research method used is a normative juridical approach by examining laws and regulations related to ASN neutrality and case studies of violations that occurred in several elections. The results show that ASN involvement in practical politics not only violates regulations but also has negative implications for electoral integrity, the principle of equal political rights, and public trust in democracy. From a constitutional law perspective, ASN neutrality is part of the realization of the principles of the rule of law and constitutional democracy. Therefore, strengthening legal instruments, optimizing oversight functions, and implementing strict sanctions are needed to uphold ASN neutrality while strengthening the quality of democracy in Indonesia.